Pengaruh Komitmen Organisasi terhadap Organizational Citizenship Behavior (OCB) PT X Bandung - Albert Kurniawan (Universitas Kristen Maranatha, 2015)
The objective of this study to determine the effect of organizational commitment on Organizational Citizenship Behavior (OCB).T he samples at PT X Bandung, a state own company dealing with electrical power with 54 employees.Thedata was collected using 32 questionnaire. Deleted the validity, reliability, normality, multicolinnearity, heteroskedasticity, and hypothesis are test using IBM SPSS 21. The hypotesis of the problem in this research is : the organizational commitment has significant relationship with OCB, simultaneously, and partially.The results showed that: simultaneously, organizational commitment has significant effect on OCB. However, partially, among the dimensions of organizational commitment has not significant except normative commitment which havesignificant effect on OCB.Keywords: Organizational Citizenship Behavior (OCB), Organizational Commitment, Normative Commitment